2016
DOI: 10.1590/s1806-92902016000300002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementing growing-finishing pig diets with Bacillus spp. probiotic on growth performance and meat-carcass grade qualitytraits

Abstract: Seventy five pigs [(Landrace × Yorkshire) × Duroc] with an initial body weight of 23.3±1.40 kg were used in the present study to investigate the influence of supplementation of a Bacillus spp. combination as probiotic (0%, 0.01%, and 0.02% with basal diet) in growing-finishing pig diets on performance parameters with a feeding trial period of 16 weeks. Growth performance was analyzed at the start and at weeks 6, 12, and 16 of the experimental period. The entire experiment using probiotic supplementation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
47
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 34 publications
10
47
2
Order By: Relevance
“…This may be due to the microbiota balance in the gut being optimised, resulting in an improved utilisation of nutrients and reduced diarrhoea score. In this study, modest but statistically significant effects on Lactobacilli and E. coli counts were observed in faecal after pigs were fed with supplemented MSP, which are in agreement with Balasubramanian et al (2016) and Yan and Kim (2013) who reported that inclusion of dietary probiotic increased the faecal Lactobacillus and decreased E. coli counts in growing-finishing pigs. Thus, it may the reason behind reduced diarrhoea incidence in pigs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This may be due to the microbiota balance in the gut being optimised, resulting in an improved utilisation of nutrients and reduced diarrhoea score. In this study, modest but statistically significant effects on Lactobacilli and E. coli counts were observed in faecal after pigs were fed with supplemented MSP, which are in agreement with Balasubramanian et al (2016) and Yan and Kim (2013) who reported that inclusion of dietary probiotic increased the faecal Lactobacillus and decreased E. coli counts in growing-finishing pigs. Thus, it may the reason behind reduced diarrhoea incidence in pigs.…”
Section: Discussionsupporting
confidence: 92%
“…According to Meng et al (2010), MSP could increase the ATTD in the growing phase, but not in the finishing phase of pigs. Moreover, Balasubramanian et al (2016) reported that Bacillus spp. probiotic in diets significantly increased nutrient digestibility in growing-finishing pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of Lactobacillus species and Bifidobacterium species were increased in the feces of growing pigs fed Bacillus species-based probiotics [26]. A linear trend of Bacillus species-based probiotics supplementation on the number of Lactobacillus species was found [21]. Dietary supplementation of B. licheniformis in combination with B. subtilis reprograms the microbiota of weaning piglets challenged with F4 positive enterotoxigenic E. coli.…”
Section: Discussionmentioning
confidence: 95%
“…A previous study demonstrated that a dietary combination of Bacillus species-based probiotics, containing B. lichenformis, B. coagulans, and B. subtilis, improves the growth performance in growing-finishing pigs [21]. It has been demonstrated that supplementation of B. licheniformis in combination with B. subtilis increases the growth performance and reduces the morbidity and mortality rates associated with diarrhea in weaning piglets [22].…”
Section: Discussionmentioning
confidence: 99%
“…As result animals may have increased growth performance because they eat more. We also investigated whether a specific synbiotic, a combination of SuperYea and multi-strain probiotic have a higher effect on body final weight gain, body weight gain and average daily gain compared to other treatments for growing pigs (p<0.05) but average daily feed intake had not significant(p>0.05) as similarly with [5,[17][18][19] were studied of supplementation of yeast culture (YC) and modified yeast culture [YC+cell wall product (CWP) containing mannam-oligosaccharide] were increased body weight gain (BW) compared to control (p<0.05) but the average dairy feed intake (ADFI) had not significant among treatments (p>0.05). The supplementation of a prebiotics did not significantly affect growth.…”
Section: Discussionmentioning
confidence: 99%